Páramo de Papallacta - A physiogeographical map 1:50,000 of the area around the Antisana (Eastern Cordillera of Ecuador) - Lauer, Wilhelm; Rafiqpoor, M. Daud (ERDKUNDE, 2000)
With this map the authors present to the International Mountain Research Society a further example of high mountain cartography (Lauer a. Rafiqpoor 1990). Due to the specific abundance of physiogeographical details the map provides a solid basis for scientific spatial interpretation. This is also the main feature of the presented map compared with the topographic maps of the Ecuadorian IGM, which are based on a very poor legend. In the study area of this map we distinguish three marked geoecologically different units. We describe the geological, geomorphological, climatological and, with particular emphasis, the phytogeographical features and the land-use types of these sections. Finally we consider the issue of the potential timberline of the equatorial study area in Ecuador, with a focus on the timberline problems in the tropical Andean high mountains.